Wellness Innovation Lab : Workshop Guidebook - Leading English Education and Resource Network (LEARN); Percolab Coop (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)
Number of pages: 28

Resolution 2022-03 : A Call to Suspend and Amend Law 21 - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2021-07 : Addressing the Issue of the Teacher Shortage in Quebec - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)
Number of pages: 1

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)
Number of pages: 28

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)
Number of pages: 28

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Le Canada de Minnie H. Bowen : Cahier de l'enseignant pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Le Canada de Minnie H. Bowen : Cahier de l'enseignant pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Loyalistes : Le développement des Cantons-de-l'Est par les Loyalistes : Cahier de l'enseignant pour le primaire - Eastern Townships Resource Centre (ETRC) (2019)

Loyalistes : Le développement des Cantons-de-l'Est par les Loyalistes : mythe ou réalité ? : Cahier de l'enseignant pour le secondaire - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Loyalists : The Development of the Eastern Townships by the Loyalists : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for elementary school - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Update - Leading English Education and Resource Network (LEARN) (2012)

Wild Berrylicious : Youth School Kit - Coasters Association (2012)